Preparation method of nitrogen-doped carbon nanotube wave-absorbing material filled with Fe7S8-FeS2

By preparing nitrogen-doped carbon nanotube absorbing materials filled with Fe7S8/FeS2, the problems of unclear dielectric modulation and narrow absorption bandwidth of transition metal sulfide absorbing materials were solved, achieving a wide-band, strong absorption effect for electromagnetic waves, which is suitable for large-scale production.

CN119264719AInactive Publication Date: 2025-01-07UNIV OF ELECTRONICS SCI & TECH OF CHINA

Patent Information

Application Number
CN202411382091.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The dielectric modulation mechanism of transition metal sulfide microwave absorbing materials is unclear, resulting in a narrow electromagnetic wave absorption bandwidth and weak absorption intensity.

Method used

Nitrogen-doped carbon nanotubes filled with Fe7S8/FeS2 were prepared by adjusting the microstructure and structure of transition metal sulfides using a simple chemical synthesis method. This method involved reacting dicyandiamide and ferric chloride in deionized water, followed by annealing in a tube furnace to form Fe/nitrogen-doped carbon nanotubes. These nanotubes were then mixed with sulfur powder to finally obtain Fe7S8/FeS2-filled nitrogen-doped carbon nanotubes.

Benefits of technology

It achieves electromagnetic wave absorption performance with wide bandwidth, strong absorption, and thin matching thickness, with a maximum reflection loss of -36.83dB and an effective absorption bandwidth of 5.14GHz. The material preparation is simple and cost-controllable, making it suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264719A_ABST
    Figure CN119264719A_ABST
Patent Text Reader

Abstract

The invention relates to the field of inorganic nano composite materials, and provides a preparation method of a nitrogen-doped carbon nanotube wave-absorbing material filled with Fe7S8-FeS2. The method aims at solving the technical problems that the dielectric regulation and control mechanism of a transition metal sulfide wave-absorbing material is not clear, the electromagnetic wave absorption frequency band is narrow, and the absorption strength is low. According to the main scheme, the method comprises the following steps: dissolving dicyandiamide and ferric chloride in deionized water, and heating and drying to obtain red powder; annealing the powder to obtain Fe / nitrogen-doped carbon nanotube black powder; after mixing with sulfur powder, annealing again to obtain Fe7S8 / nitrogen-doped carbon nanotube black powder; and finally, mixing and annealing with sulfur powder to obtain the Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube wave-absorbing material. The material shows excellent absorption strength and absorption bandwidth under the condition of low thickness (1.6 mm), the maximum reflection loss is-36.83 dB, and the effective absorption bandwidth is 5.14 GHz (11.9-17.04 GHz). The invention also provides application of the material, namely the material is used as a wave-absorbing material, and is mixed with paraffin or epoxy resin and then coated on the surface of a protected object.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of inorganic nanocomposite materials and relates to a method for preparing a Fe7S8-FeS2-filled nitrogen-doped carbon nanotube absorbing material. Background Art

[0002] Electromagnetic pollution caused by the widespread propagation of electromagnetic waves poses a major threat to communication security and human health. In order to reduce electromagnetic interference and improve device performance, it is of great significance to study high-performance electromagnetic wave absorbing materials.

[0003] Transition metal sulfides have attracted much attention in the field of microwave absorbing materials due to their unique physicochemical properties and tunable electronic structures. As a typical transition metal sulfide, pyrite FeS2 has a high theoretical charge storage capacity, which helps to respond quickly to electromagnetic waves. It is also low-cost and environmentally friendly, making it a promising microwave absorbing material. However, most sulfide-based materials have poor electronic conductivity and poor chemical stability.

[0004] Generally speaking, there are several strategies for modifying transition metal sulfides: (a) phase control; (b) defect engineering; (c) chemical doping; and (d) layered configuration. Therefore, effectively adjusting the microscopic composition and microstructure of transition metal sulfides and enriching the microwave loss mechanism of the material are important starting points for improving the electromagnetic wave absorption performance of the material. Summary of the invention

[0005] The present invention aims to solve the technical problems of unclear dielectric regulation mechanism, narrow electromagnetic wave absorption band and weak absorption intensity of transition metal sulfide absorbing materials, and provides a method for preparing Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material, which can show excellent absorption intensity and absorption bandwidth at a low thickness (1.6mm).

[0006] To achieve the above purpose, the present invention adopts the following technical means:

[0007] A method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material is carried out according to the following steps:

[0008] Step 1, dissolving dicyandiamide and ferric chloride in deionized water, stirring to dissolve, obtaining an orange-red reaction solution, and finally heating and drying in an oil bath to obtain a red powder;

[0009] Step 2: Grind the red powder obtained in step 1 thoroughly, put it into an alumina porcelain boat, put it into a tube furnace, and heat and anneal it under an argon atmosphere to obtain Fe / nitrogen-doped carbon nanotube black powder;

[0010] Step 3, grinding the Fe / nitrogen-doped carbon nanotube powder obtained in step 2 thoroughly, mixing it with sulfur powder in a certain mass ratio, placing it in an alumina porcelain boat, placing it in a tube furnace, and heating and annealing it in an argon atmosphere to obtain Fe7S8 / nitrogen-doped carbon nanotube black powder;

[0011] Step 4: Grind the Fe7S8 / nitrogen-doped carbon nanotube powder obtained in step 3 thoroughly, mix it with sulfur powder in a certain mass ratio, place it in an alumina porcelain boat, put it into a tubular furnace, and heat and anneal it under an argon atmosphere. The obtained black powder is the Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material, and the preparation is completed.

[0012] In the above scheme, the molar ratio of dicyandiamide to ferric chloride in step 1 is 10:1, wherein the concentration of iron element is 0.01-0.05 mol / L.

[0013] In the above scheme, the heating temperature in step 1 is 75-95° C. min, the stirring speed is 300-600 rpm, and complete drying is characterized by the absence of any solvent.

[0014] In the above scheme, the drying time described in step 1 is 1.5 to 8.5 hours.

[0015] In the above scheme, the heating annealing temperature in step 2 is 700-900° C., and the heating annealing time is 1-3 hours.

[0016] In the above scheme, the mass ratio of the Fe / nitrogen-doped carbon nanotube powder to the sulfur powder in step 3 is 1:2.5 to 1:3.5.

[0017] In the above scheme, the heating annealing temperature in step 3 is 500-700° C., and the heating annealing time is 1-3 hours.

[0018] In the above scheme, the mass ratio of the Fe7S8 / nitrogen-doped carbon nanotube powder to the sulfur powder in step 4 is 1:0.6 to 1:1.4.

[0019] In the above scheme, the heating annealing temperature in step 4 is 300-500° C., and the heating annealing time is 0.5-1.5 h:

[0020] The present invention also provides an application of a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material, wherein the Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube is used as the absorbing material. s The nitrogen-doped carbon nanotube material filled with / FeS2 is used as a filler, uniformly mixed with paraffin or epoxy resin in proportion, and coated on the surface of the protected object for use as a coating.

[0021] Because the present invention adopts the above technical means, it has the following beneficial effects:

[0022] 1. Commercial chemical reagents are used to synthesize composite materials. The synthetic reagents can be used directly without further purification. The synthesis process does not require complex equipment and harsh experimental environment. The preparation process of the present invention has controllable cost, simple and repeatable process, and can achieve large-scale production. All chemical reagents are analytical grade reagents and can be used directly without further purification.

[0023] 2. A method for preparing Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material is provided.

[0024] 3. The material prepared by the method of the present invention is a wide-band, strong absorption, thin matching thickness absorbing material. When the matching thickness is 1.6 mm, the maximum reflection loss is -36.83 dB, and the effective absorption bandwidth is 5.14 GHz (11.9-17.04 GHz). The present invention provides a good design idea for transition metal sulfide / nitrogen-doped carbon nanotube absorbing materials.

[0025] 4. The Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material prepared by the method of the present invention, while in-situ nitrogen-doping the carbon nanotubes, introduces transition metal sulfide Fe7S8 / FeS2 to adjust the dielectric constant of the system, improve the impedance matching ability of the composite material, and adjust the loss ability. In addition, more nitrogen defects and Fe7S8 / FeS2 heterogeneous interfaces are introduced into the carbon nanotubes to enhance defect-induced dipole polarization and interface polarization losses. In summary, by adjusting the degree of continuous vulcanization and the content of Fe7S8 / FeS2, the dielectric properties are enhanced while good impedance matching is achieved, thereby obtaining excellent electromagnetic wave absorption performance.

[0026] The Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material prepared by the method of the present invention is applied to the field of electromagnetic wave absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM photograph of the Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material obtained in Example 1 of the present invention;

[0028] Figure 2 This is a TEM photo of the Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material obtained in Example 1 of the present invention;

[0029] Figure 3 This is a HRTEM photo of the Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material obtained in Example 1 of the present invention;

[0030] Figure 4This is the XRD spectrum of the Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material prepared in Example 1 of the present invention.

[0031] Figure 5 This is the Raman spectrum of the Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material obtained in Example 1 of the present invention.

[0032] Figure 6 This is the reflection loss spectrum of the Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0034] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0035] A method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material is carried out according to the following steps:

[0036] Step 1, dissolving dicyandiamide and ferric chloride in deionized water, stirring to dissolve, obtaining an orange-red reaction solution, and finally heating and drying in an oil bath to obtain a red powder;

[0037] Step 2: Grind the red powder obtained in step 1 thoroughly, put it into an alumina porcelain boat, put it into a tube furnace, and heat and anneal it under an argon atmosphere to obtain Fe / nitrogen-doped carbon nanotube black powder;

[0038] Step 3, grinding the Fe / nitrogen-doped carbon nanotube powder obtained in step 2 thoroughly, mixing it with sulfur powder in a certain mass ratio, placing it in an alumina porcelain boat, placing it in a tube furnace, and heating and annealing it in an argon atmosphere to obtain Fe7S8 / nitrogen-doped carbon nanotube black powder;

[0039] Step 4: Grind the Fe7S8 / nitrogen-doped carbon nanotube powder obtained in step 3 thoroughly, mix it with sulfur powder in a certain mass ratio, place it in an alumina porcelain boat, put it into a tubular furnace, and heat and anneal it under an argon atmosphere. The obtained black powder is the Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material, and the preparation is completed.

[0040] In the above scheme, the molar ratio of dicyandiamide to ferric chloride in step 1 is 10:1, wherein the concentration of iron element is 0.01-0.05 mol / L.

[0041] In the above scheme, the heating temperature in step 1 is 75-95° C. min, the stirring speed is 300-600 rpm, and complete drying is characterized by the absence of any solvent.

[0042] In the above scheme, the drying time described in step 1 is 1.5 to 8.5 hours.

[0043] In the above scheme, the heating annealing temperature in step 2 is 700-900° C., and the heating annealing time is 1-3 hours.

[0044] In the above scheme, the mass ratio of the Fe / nitrogen-doped carbon nanotube powder to the sulfur powder in step 3 is 1:2.5 to 1:3.5.

[0045] In the above scheme, the heating annealing temperature in step 3 is 500-700° C., and the heating annealing time is 1-3 hours.

[0046] In the above scheme, the mass ratio of the Fe7S8 / nitrogen-doped carbon nanotube powder to the sulfur powder in step 4 is 1:0.6 to 1:1.4.

[0047] In the above scheme, the heating annealing temperature in step 4 is 300-500° C., and the heating annealing time is 0.5-1.5 h:

[0048] The present invention also provides an application of a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material. The Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube is used as an absorbing material. The Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube material is used as a filler, uniformly mixed with paraffin or epoxy resin in proportion, and coated on the surface of the protected object to be used as a coating.

[0049] Specific implementation method 1: This implementation method is a method for preparing a Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material, which is carried out according to the following steps:

[0050] Step 1: dissolve dicyandiamide and ferric chloride in deionized water, stir and dissolve to obtain an orange-red reaction solution; finally, place in an oil bath and heat to dry to obtain a red powder.

[0051] Step 2: Grind the red powder obtained in step 1 thoroughly, put it in an alumina porcelain boat, put it in a tube furnace, and heat and anneal it in an argon atmosphere to obtain Fe / nitrogen-doped carbon nanotube black powder.

[0052] Step 3: Grind the Fe / nitrogen-doped carbon nanotube powder obtained in step 2 thoroughly, mix it with sulfur powder in a certain mass ratio, place it in an alumina porcelain boat, put it in a tubular furnace, and heat and anneal it in an argon atmosphere to obtain Fe7S8 / nitrogen-doped carbon nanotube black powder.

[0053] Step 4: Grind the Fe7S8 / nitrogen-doped carbon nanotube powder obtained in step 3 thoroughly, mix it with sulfur powder in a certain mass ratio, place it in an alumina porcelain boat, put it into a tubular furnace, and heat and anneal it under argon atmosphere. The obtained black powder is the Fe7S8 / FeS2 / nitrogen-doped carbon nanotube absorbing material, and the preparation is completed.

[0054] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the molar ratio of dicyandiamide to ferric chloride in step 1 is 10:1, wherein the concentration of iron element is 0.01-0.05 mol / L. Other aspects are the same as those in specific embodiment 1.

[0055] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the heating temperature in step 1 is 75-95°C min, the stirring speed is 300-600 rpm, and complete drying means the absence of any solvent. Other aspects are the same as specific embodiment 1 or 2.

[0056] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the drying time in step 1 is 1.5 to 8.5 hours. The rest is the same as specific embodiments 1 to 3.

[0057] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the heating annealing temperature in step 2 is 700-900° C. The rest is the same as specific embodiments 1 to 4.

[0058] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the heating annealing time in step 2 is 1 to 3 hours. The rest is the same as specific implementation methods 1 to 5.

[0059] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 3, the Fe / nitrogen doped carbon nanotube powder and sulfur powder are in a certain mass ratio of 1:2.5 to 1:3.5. The rest is the same as specific embodiments 1 to 6.

[0060] Specific embodiment 8: This embodiment is different from specific embodiments 1 to 7 in that the heating annealing temperature in step 3 is 500-700° C. The rest is the same as specific embodiments 1 to 7.

[0061] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the heating annealing time in step 3 is 1 to 3 hours. The rest is the same as specific embodiments 1 to 8.

[0062] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the Fe7S8 / nitrogen-doped carbon nanotube powder and sulfur powder in step 4 are in a certain mass ratio of 1:0.6 to 1:1.4. The rest is the same as specific embodiments 1 to 9.

[0063] Specific embodiment eleven: This embodiment differs from specific embodiments one to ten in that the heating annealing temperature in step four is 300-500° C. The rest is the same as specific embodiments one to ten.

[0064] Specific embodiment 12: This embodiment differs from specific embodiments 1 to 11 in that the heating annealing time in step 4 is 0.5 to 1.5 hours. The rest is the same as specific embodiments 1 to 11.

[0065] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0066] Embodiment 1:

[0067] This embodiment provides a method for preparing a Fe7S8 / FeS2 filled nitrogen-doped carbon nanotube absorbing material, which is carried out according to the following steps:

[0068] Step 1: Dissolve 250 mg of dicyandiamide and 50 mg of ferric chloride in 10 mL of deionized water, stir to dissolve, and obtain an orange-red reaction solution; finally, place in an 80°C oil bath, stir at 500 rpm, and heat to dry for 8 hours to obtain a red powder.

[0069] Step 2: Grind the red powder obtained in step 1 thoroughly, put it in an alumina porcelain boat, put it into a tube furnace, and anneal it at 800° C. for 2 h under an argon atmosphere to obtain Fe / nitrogen-doped carbon nanotube black powder.

[0070] Step 3: Grind the Fe / nitrogen-doped carbon nanotube powder obtained in step 2 thoroughly, mix it evenly with sulfur powder in a mass ratio of 1:3, place it in an alumina porcelain boat, put it into a tubular furnace, and anneal it at 600°C for 2h under an argon atmosphere to obtain Fe7S8 / nitrogen-doped carbon nanotube black powder.

[0071] Step 4: Grind the Fe7S8 / nitrogen-doped carbon nanotube powder obtained in step 3 thoroughly, mix it evenly with sulfur powder in a mass ratio of 1:1, place it in an alumina porcelain boat, put it into a tubular furnace, and anneal it at 400°C for 1h under argon atmosphere. The obtained black powder is the Fe7S8 / FeS2 / nitrogen-doped carbon nanotube absorbing material, and the preparation is completed.

[0072] Preparation of test samples:

[0073] The Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material prepared in Example 1 was placed in paraffin at a mass ratio of 15%, heated to 80°C, and kept warm for 10 minutes. The sample was placed in a mold to finally obtain a coaxial ring with an outer diameter of 7 mm, an inner diameter of 3.04 mm, and a height of 1.6 mm.

Claims

1. A method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material, characterized in that: It is carried out in the following steps: Step 1, dissolving dicyandiamide and ferric chloride in deionized water, stirring to dissolve, obtaining an orange-red reaction solution, and finally heating and drying in an oil bath to obtain a red powder; Step 2: Grind the red powder obtained in step 1 thoroughly, put it into an alumina porcelain boat, put it into a tube furnace, and heat and anneal it under an argon atmosphere to obtain Fe / nitrogen-doped carbon nanotube black powder; Step 3, grinding the Fe / nitrogen-doped carbon nanotube powder obtained in step 2 thoroughly, mixing it with sulfur powder in a certain mass ratio, placing it in an alumina porcelain boat, placing it in a tube furnace, and heating and annealing it in an argon atmosphere to obtain Fe7S8 / nitrogen-doped carbon nanotube black powder; Step 4: Grind the Fe7S8 / nitrogen-doped carbon nanotube powder obtained in step 3 thoroughly, mix it with sulfur powder in a certain mass ratio, place it in an alumina porcelain boat, put it into a tubular furnace, and heat and anneal it under an argon atmosphere. The obtained black powder is the Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube absorbing material, and the preparation is completed.

2. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: The molar ratio of dicyandiamide to ferric chloride in step 1 is 10:1, wherein the concentration of the iron element is 0.01-0.05 mol / L.

3. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: The heating temperature in step 1 is 75-95° C. min, the stirring speed is 300-600 rpm, and complete drying is characterized by the absence of any solvent.

4. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: The drying time in step 1 is 1.5 to 8.5 hours.

5. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: The heating annealing temperature in step 2 is 700-900° C., and the heating annealing time is 1-3 hours.

6. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: In step 3, the mass ratio of the Fe / nitrogen-doped carbon nanotube powder to the sulfur powder is 1:2.5 to 1:3.

5.

7. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: The heating annealing temperature in step 3 is 500-700° C., and the heating annealing time is 1-3 hours.

8. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: In step 4, the mass ratio of the Fe7S8 / nitrogen-doped carbon nanotube powder to the sulfur powder is 1:0.6 to 1:1.

4.

9. The method for preparing a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material according to claim 1, characterized in that: The heating annealing temperature in step 4 is 300-500° C., and the heating annealing time is 0.5-1.5 h.

10. The use of a Fe7S8-FeS2 filled nitrogen-doped carbon nanotube absorbing material as claimed in claim 1, characterized in that: The Fe7S8 / FeS2-filled nitrogen-doped carbon nanotubes are used as absorbing materials. The Fe7S8 / FeS2-filled nitrogen-doped carbon nanotube material is used as a filler, uniformly mixed with paraffin or epoxy resin in proportion, and coated on the surface of the protected object to be used as a coating.

Citation Information

Patent Citations

  • Carbon nanotube composite material filled with ferrous sulfide, preparation method and application thereof

    CN102010690A

  • Preparation method of nitrogen-doped carbon nanotube wrapped metal iron-cobalt alloy composite material

    CN108160077A

  • Iron-containing self-loaded nitrogen-doped carbon nanotube oxygen reduction catalyst as well as preparation method and application thereof

    CN112751048A

  • Preparation method of biomass-based graphitized carbon / Fe7S8 composite material

    CN113036099A

  • Core-Shell Structured Composite Powder Electromagnetic Wave Absorber Formed by Coating Fe-Based Nanocrystalline Alloy with Carbon, and Preparation Method Thereof

    US20220380609A1

Cited By

  • Fe7S8 doped material based on transition metal in pyrite as well as preparation method and application of Fe7S8 doped material

    CN120698510A